Pembelajaran Berbasis Kurikulum Merdeka pada Program Keahlian Akuntansi dan Keuangan Lembaga Kelas XI di SMK Negeri 1 Banyudono - Diman, Vinna Idamtus Silmi; Syah, Muhammad Fahmi Johan (Universitas Muhammadiyah Surakarta, 2023)
The rapid development of the world of education has encouraged changes in the curriculum in Indonesia, one of which is the Merdeka Curriculum